Nutrition for child and adolescent athletes - Bar-Or, O. (2000)
* To facilitate growth and development, the daily protein requirements per unit body weight are higher for children than for adults, but it is unclear whether child athletes need more protein than their inactive counterparts for normal growth and development and for optimal performance. * Children require more energy than do adolescents or adults during sports activities that include walking or running, and possibly in other activities. * Compared with adults, children and adolescents use more fat and less carbohydrate during prolonged exercise. * Special attention must be paid to prevent voluntary dehydration in children who exercise in hot/humid climates. To encourage further drinking, a beverage should be tasty and include glucose and small amounts of sodium chloride.